Clinical effects of cervical conization with positive margins in cervical cancer - Yukari Nagao (Nature Portfolio, 2021)
Abstract Radical surgery after cervical conization is a common approach for the treatment of cervical cancer. In some cases, disease progression is observed after positive margins at conization, but the effect of conization on disease progression remains unclear. Thus, the aim of this study was to investigate the clinical outcomes of positive margins at conization in cervical cancer. A total of 101 patients who underwent cervical conization before radical hysterectomy and pelvic lymph node dissection were considered eligible by reviewing medical records. The association between the positive margins and patient outcomes, including subsequent lymph node metastasis, was evaluated. The rate of lymphovascular space invasion (LVSI) positivity at radical surgery was significantly higher in patients with positive margins (p = 0.017) than in those with negative margins, although there was no significant difference in the rate of pelvic lymph node metastasis (p = 0.155). Moreover, there was no significant difference in the overall survival or progression-free survival between the two groups (p = 0.332 and 0.200, respectively). A positive margin at conization presented no significant prognostic disadvantage; thus, diagnostic conization is one of the most suitable treatment options for early-stage cervical cancer that is difficult to accurately assess.